(untitled) (Al-Academy, 2025)
The researcher tried to show the impact of environmental and community issues and embody the vital role of the constant and variable and what has become of contemporary trends and their interaction with each other and reflect this interaction in the creation of new technical methods that require research and deep treatment by asking: What is the environmental Demonstration between the constant and the variable in the work of ceramics? The research focuses on the work of the artist Sajida Al-Mashaikhi in particular, which provides an in-depth study of her artistic orientations and seeks towards enhancing awareness of environmental issues through art, which may be far from other studies, and then determine the importance of research and its need, and confirm the specific research goal by revealing the environmental Demonstration between the constant and variable in the ceramic works of Sajida Al-Mashaikhi. The most important and prominent indicators for analyzing research samples, including that the essence of assets is constant and reality is variable in new textile structures is governed at every moment by the factor of time. The third chapter explained the presentation of research procedures with the research community and its sample, determining the descriptive approach and analyzing the selected research sample with three ceramic models ((Arabic letter, heritage, horses)), The analysis tool is based on observation. They change according to the nature of the forms.